2019
DOI: 10.1111/acv.12519
|View full text |Cite
|
Sign up to set email alerts
|

Allopatric divergence drives the genetic structuring of an endangered alpine endemic lizard with a sky‐island distribution

Abstract: Anthropogenic climate change is causing a world-wide reduction of alpine habitat, leaving many high-elevation species restricted to sky-islands and vulnerable to extinction. Understanding the genetic parameters of these populations provides key insight into species diversity, dispersal capacity and vulnerability to disturbance. We examined the impact of past climatic variation on a threatened alpine endemic lizard, the Guthega skink, Liopholis guthega. We analysed SNP and mtDNA data to determine the population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Recent dietary analysis between the two populations revealed an almost identical foraging ecology, with consistent temporal variation (Atkins et al 2018), suggesting that diet is not driving the life history variation seen here. It is possible that the marked differences maybe a result of the phylogeographic differences documented between the two populations (Atkins et al, 2019), as has been suggested elsewhere (e.g. Du et al, 2005).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Recent dietary analysis between the two populations revealed an almost identical foraging ecology, with consistent temporal variation (Atkins et al 2018), suggesting that diet is not driving the life history variation seen here. It is possible that the marked differences maybe a result of the phylogeographic differences documented between the two populations (Atkins et al, 2019), as has been suggested elsewhere (e.g. Du et al, 2005).…”
Section: Discussionmentioning
confidence: 69%
“…It is a true alpine specialist whose entire range is restricted to two geographically isolated sky islands above 1600 m in south-eastern Australia: the Bogong High Plains (BHP) in Victoria (Vic), and Kosciuszko National Park (KNP) in New South Wales (NSW) (Donnellan et al, 2002;Atkins et al, 2018). The two populations are separated by̴ 100 km of lowland valleys that completely impede gene flow, and represent an estimated one million years of allopatry (Atkins et al, 2019;Chapple, Keogh & Hutchinson, 2005). Furthermore, at a local scale, discrete colonies exhibit high genetic structure due to natural habitat barriers (alpine bog systems), further reducing gene flow and population viability (Atkins et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mechanism is involved in transitions between GSD and TSD (Quinn et al., 2011), and our population genetic data demonstrate that isolation by distance is the primary pattern of genetic differentiation in this species, providing a pattern of underlying genetic variation. In contrast to other reptiles with very large species distributions, P. vitticeps has no obvious barriers to dispersal and no significant population structure (Atkins et al, 2019; Melville et al., 2001, 2017; Sovic et al., 2016). The Murray River in South Australia was the only weak and porous barrier to dispersal that we detected.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the thermal quality of the environment may affect dispersal, predation and resource availability, as reported in the alpine sheoak skink (C. praealtus) and Guthega skink (Liopholis guthega; Sato et al 2014a). These species are alpine endemics, confined to two main regions within the Australian mainland alps (Koumoundouros et al 2009;Atkins et al 2020). The isolation of the highelevation environment in Australia has facilitated high rates of endemism within this region, and several species are listed as Threatened (e.g.…”
Section: Introductionmentioning
confidence: 99%